1988
DOI: 10.1080/07391102.1988.10506489
|View full text |Cite
|
Sign up to set email alerts
|

IR and UV Studies on Stability and Conformations of Short DNA Duplexes Containing a No-Base Residue: Coexistence of B and Z Conformations

Abstract: Tridecamers containing a central no-base residue (X) have been synthesized and hybridized to their complementary strands, so as to constitute duplexes consisting of two hexamers separated by central mismatched X-A or X-T pairs. The effect of the introduction of this deoxyribose derivative on duplex stability was investigated by measuring UV absorbance as a function of salt concentration and temperature. As expected, the duplexes containing the abnormal base pairs (X-T and X-A) are less stable when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Arnott et al (1983) were able to construct models of B-DNA embedded within a patch of Z-DNA as well as of B-DNA embedded within a patch of A-DNA, with only one base pair adopting a different conformation; both of these models were found to involve bending or kinking at the junction region. Subsequently, a B-Z junction has been observed in both natural DNA (Rich et al, 1984) and synthetic DNA oligomers (Sheardy, 1988;Adam et al, 1988), and a cell protein capable of binding to Z-DNA has also been reported (Leith et al, 1988). The possibility of a B-DNA/A-DNA junction in vivo was suggested by Rhodes and Klug (1986), who proposed that the DNA-binding site for transcriptional factor IIIA (TFIIIA) in the Xenopus 5S RNA gene region has an A-like structure on the basis of the observation that TFIIIA can bind to its target site in the double-stranded DNA structural gene as well as to the RNA transcript.…”
mentioning
confidence: 99%
“…Arnott et al (1983) were able to construct models of B-DNA embedded within a patch of Z-DNA as well as of B-DNA embedded within a patch of A-DNA, with only one base pair adopting a different conformation; both of these models were found to involve bending or kinking at the junction region. Subsequently, a B-Z junction has been observed in both natural DNA (Rich et al, 1984) and synthetic DNA oligomers (Sheardy, 1988;Adam et al, 1988), and a cell protein capable of binding to Z-DNA has also been reported (Leith et al, 1988). The possibility of a B-DNA/A-DNA junction in vivo was suggested by Rhodes and Klug (1986), who proposed that the DNA-binding site for transcriptional factor IIIA (TFIIIA) in the Xenopus 5S RNA gene region has an A-like structure on the basis of the observation that TFIIIA can bind to its target site in the double-stranded DNA structural gene as well as to the RNA transcript.…”
mentioning
confidence: 99%